EUROPEAN ASSOCIATION AGREEMENTS AND SOME ASPECTS OF GEORGIA ECONOMICS - Lali Chagelishvili-Agladze; Simon Amiran Tavartkiladze; Lia Totladzde; Tamar Agladze (European Scientific Journal, ESJ, 2014)
Association agreement between the EU and Georgia, unlike the prior similar agreements, takes into account very important mechanisms of real convergence with European Union, European legislation and standards. Association Agreement with the European Union does not imply affiliation, (ex. Turkey an association agreement was signed in 1960, but the country is still not an EU member). However, an Association Agreement with the EU legislation implies such a high level of convergence that the effective implementation of the Europeanization process is irreversible. In addition, the Association Agreement with the European Union is the real mechanism of political association and gradual economic integration. However, it should be understood that the agreement is contributing to a lot of things, many of which gives rise to liability. For the proper execution of agreement relevant levers like many aspects of Georgian economy, trade policy and legislation, which we will discuss in this paper, are required.